(untitled) (Bangladesh Journal of Zoology, 2026)
A total of 350 Rita rita were examined from January 2018 to December 2019 for investigations on parasite infestation and proximate composition. From R. rita, a total of nine species of parasites were recovered and identified, including one ecto-parasite (Lernaea cyprinacea) and eight endo-parasites. Among the endo-parasites, there were four trematodes (Notoporus leiognathi, Saccacoelium obesum, Sterrhurus musculus and Clinostomum piscidium), one nematode (Ascaroid larva) and three acanthocephalans (Cavisoma magnum, Corynosoma alaskense and Corynosoma strumosum). The parasite community was dominated by trematodes and acanthocephalans comprising 59.12% and 31.99% of the total number of helminth parasites dominated by Notoporus leiognathi (18.26%) trematodes. The prevalence of infestation of ecto-parasite was 24.8% (87 specimens) and mean intensity was 3.34 ± 1.62 per infested fish. The prevalence of infestation of endo-parasites was 64.57% (226 specimens) with intensity 2.64 ± 1.12. The observation on biochemical analysis of R. rita presented small variation in nutrient contents. Protein (17.11%), fat (6.07%), moisture (74.09%), carbohydrate (3.95%) and ash level (1.43%) were higher in non-infected than infected fish. Bangladesh J. Zool. 53(3): 267-283, 2025